2000
DOI: 10.1111/j.1572-0241.2000.02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Alcoholic Patients With Esophageal Cancer Are Genetically Different From Alcoholics With Acute Pancreatitis and Liver Cirrhosis

Abstract: The allele frequency of ADH2*1 and ALDH2*1 are different among subpopulations of alcoholics, suggesting that alcoholic patients with different specific types of organ damage are genetically different. The Chinese alcoholic patients with the ADH2*1 and ALDH2*2 allele are more susceptible to esophageal Ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 17 publications
1
51
1
Order By: Relevance
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…The hazard ratio of hospitalization for alcoholism in men and women with the slow alcohol degradation ADH1B Á 1/1 genotype was 3.9 (95% CI: 1.0-16) and 2.7 (95% CI: 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, persons with combined genotypes of ADH2 G/G and ALDH2 G/A are at a high risk of developing esophageal squamous cell carcinoma. Chao et al [14] reported that Chinese alcoholic patients with ADH2 G and ALDH2 A alleles are more susceptible to esophageal cancer. However, Ohhira et al [15] showed that 10 patients with hepatocellular carcinoma (HCC) associated with pure alcoholic liver disease all have ALDH2 G/G genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, when ADH2 activity is increased or ALDH2 activity is decreased, the blood acetaldehyde level also increases in drinkers, thus increasing the risk of developing colorectal cancer. However, inconsistent results have been reported in many studies on the relation between ADH2 and ALDH2 gene polymorphisms and cancer susceptibility [11][12][13][14][15][16][17][18] . Yokoyama et al [11] found ALDH2 G/A genotype encoding inactive ALDH2 and ADH2 G/G genotype encoding the low-activity form of ADH2 can enhance the risk of esophageal cancer in Japanese alcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most studies, conducted mainly in Japan, have revealed associations between the ADH2 or ALDH2 polymorphism and esophageal cancer risk. [4][5][6][7][8] Chao et al 9 found that Chinese alcoholic patients with the ADH2 G and ALDH2 A alleles were more susceptible to esophageal cancer. Wu et al 10 also found a multiplicative effect of lifetime alcoholic consumption and genotypes (ADH2 and ALDH2) on esophageal cancer risk, but those were only found in Taiwanese males.…”
Section: Introductionmentioning
confidence: 99%